2009
DOI: 10.1158/0008-5472.can-09-1752
|View full text |Cite|
|
Sign up to set email alerts
|

Glomus Tumors in Neurofibromatosis Type 1: Genetic, Functional, and Clinical Evidence of a Novel Association

Abstract: Neurofibromatosis type 1 (NF1) is a common disorder that arises secondary to mutations in the tumor suppressor gene NF1. Glomus tumors are small, benign but painful tumors that originate from the glomus body, a thermoregulatory shunt concentrated in the fingers and toes. We report 11 individuals with NF1 who harbored 20 glomus tumors of the fingers and 1 in the toe; 5 individuals had multiple glomus tumors. We hypothesized that biallelic inactivation of NF1 underlies the pathogenesis of these tumors. In 12 NF1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 41 publications
4
87
0
2
Order By: Relevance
“…The tumors arise from the glomus body, a highly innervated thermoregulatory shunt containing concentric layers of contractile ␣-actin-positive glomus cells, which harbor bi-allelic inactivation of the NF1 gene. 74 Glomus tumors may affect up to 5% of the adult NF1 patient population. 75 Neurofibromas are lesions characterized by bi-allelic inactivation of the NF1 gene in a subpopulation of Schwann cells.…”
Section: Nf1 Lesions Caused By Loh or Somatic Second-hit Mutationsmentioning
confidence: 99%
“…The tumors arise from the glomus body, a highly innervated thermoregulatory shunt containing concentric layers of contractile ␣-actin-positive glomus cells, which harbor bi-allelic inactivation of the NF1 gene. 74 Glomus tumors may affect up to 5% of the adult NF1 patient population. 75 Neurofibromas are lesions characterized by bi-allelic inactivation of the NF1 gene in a subpopulation of Schwann cells.…”
Section: Nf1 Lesions Caused By Loh or Somatic Second-hit Mutationsmentioning
confidence: 99%
“…RAS mitogen-activated protein kinase (MAPK) hyperactivity was found in cultured glomus cells, which lack Nf-1 -/-. The cells from the glomus tumours in the report by Brems et al [8] showed increased activation of extracellular-regulated kinases 1 and 2 (ERK1/2) phosphorylation (p-ERK1/2) after stimulation with acidic fibroblast growth factor (aFGF) in the Nf-1-associated glomus tumour-erived glomus cells. An increased p-ERK:ERK ratio was therefore detected.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous report, eight of the 11 patients were women aged 26-59 years, and a girl of 11 years [8]. Recently, a case of a painful glomus tumour of the thumb in an 11-year-old boy, on whom initially a neurofibroma of the terminal sensory branch of the digital nerve had been suspected [10], was reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…28 A associação entre a NF1 e os tumores glómicos foi definitivamente confirmada quando se detetou a inativação do gene NF1 nas células destes tumores benignos. 29 A origem é vascular, derivando do corpo glómico, responsável pela regulação local do fluxo sanguíneo nos capilares. Localizam-se mais frequentemente nas regiões acrais, particularmente nos dedos, região periungueal ou subungueal.…”
Section: Revista Spdv 75(1) 2017; Manifestações Cutâneas Das Rasopatiunclassified